Is the Electricity Sector a Weak Link in Development? - Jonathan Colmer; David Lagakos; Martin Shu (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper asks whether increasing productivity in the electricity sector can yield larger long-run GDP gains than suggested by electricity's small share of aggregate economic activity. We answer this question using a dynamic model in which electricity is a strong complement to other inputs in production. We parameterize the model using our own new measures of electricity-sector TFP across countries. The model predicts modest long-run GDP gains from improving electricity-sector TFP, contrary to the notion that electricity is a weak link. Parameterizations that make electricity a weak link mostly require the electricity sector to be counterfactually large or unproductive.
Keywords: O40; O11; Q43; 330; electricity; economic development; weak link; TFP